The PPAT'S Responsibilities on Calculation of Tax Payment Value - Rina Widoastuti; Siti Rodhiyah Dwi Istinah (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
In the implementation of the transfer of rights through the buying and selling process, at the stage of calculating the value of tax payments several times, people found that they deliberately and openly asked to reduce the transaction value from the price it should have been, so that tax costs would not be large. This writing aims to determine and analyze the calculation of the value of the sale and purchase of land and/or buildings in Pekalongan Regency, the role and responsibility of PPAT in calculating the value of tax payments based on Perda No. 6 of 2012 Pekalongan Regency. This research approach uses a sociological juridical, namely research through a legal approach and examines laws that have problems in practice. Then analyzed using role theory, responsibility theory, justice theory, and legal certainty theory. The results of the study indicate that the calculation of the value of the sale and purchase of land and/or buildings in Pekalongan Regency is based on calculations that have been determined by the laws and regulations. The role and responsibility of PPAT in calculating the value of tax payments on land and/or building sale and purchase transactions based on Perda Number 6 of 2012 Pekalongan Regency, namely PPAT's obligation in making a deed is first to ensure that the Land and Building Rights Acquisition Fee (BPHTB) has been paid. PPAT's responsibility is to help clients make online submissions on the website provided by the Pekalongan Regency Government.